2014
DOI: 10.1002/pssa.201431223
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of diamond electrodes for photo‐electrochemistry

Abstract: Boron doped diamond (BDD) shows high chemical stability in contact with a liquid phase even under extreme pH conditions, high electrochemical activity, and allows very stable covalent functionalization on O-or N-terminated surfaces. It is therefore an excellent electrode material for many applications such as analytics, biosensors, and purification. Furthermore, the electrodes can be covalently functionalized with photosensitive dyes to generate photo currents. However, the energetic conditions and charge tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…13 Petkov et al 16 grafted manganese phthalocyanine on nanocrystalline BDD and obtained photocurrents of several tens of nA cm À2 upon monochromatic illumination with 770 nm light, but the currents were anodic (h + were assumed to be transferred to the LUMO of the excited dye). For the same system, Bechter et al 17 observed cathodic photocurrent, as expected for the p-type BDD.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…13 Petkov et al 16 grafted manganese phthalocyanine on nanocrystalline BDD and obtained photocurrents of several tens of nA cm À2 upon monochromatic illumination with 770 nm light, but the currents were anodic (h + were assumed to be transferred to the LUMO of the excited dye). For the same system, Bechter et al 17 observed cathodic photocurrent, as expected for the p-type BDD.…”
Section: Introductionsupporting
confidence: 63%
“…39,40 This dispersion was often reported on various diamond electrodes, 36,38,41,42 including the diamond electrodes which were modified by light-harvesting dyes. 17 For the equivalent circuit shown in Fig. 3 (inset), the capacitance C is equal to the capacitance of the space-charge layer in the diamond electrode, that is C = C sc .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an inelastic mean free path of 1.8 nm based on experimental measurements in nanocrystalline diamond [16]. This frequency is commonly used for the characterization of diamond surfaces in aqueous solutions [17].…”
Section: Semmentioning
confidence: 99%
“…The surface termination has a strong influence on the electroanalytical performance of BDD. For example, nanocrystalline NH 2 ‐terminated BDD exhibits an improved sensitivity in comparison to oxygen‐terminated BDD . For amino‐terminated BDD, sufficient stability of the termination and an enhanced electron transfer rate in comparison to oxygen‐terminated BDD has been reported .…”
Section: Introductionmentioning
confidence: 99%